Cover, Content, and Editorial Note from Borneo J Pharm Vol. 2 No. 1 May 2019 - Chief Editor of Borneo J Pharm (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2019)
Starting from this edition, Borneo J Pharm makes changes to the template in the article that will be published. The amendment aims to make it easier for readers to observe essential parts of each page of the article.In this edition, we succeeded in obtaining several achievements, including publishing all English-language articles and successfully gaining support from several international reviewers from various countries, such as Brunei Darussalam, Russia, India and Libya. We will ensure this achievement as a start and will continue to improve the quality of Borneo J Pharm in the future.This journal aims to publish high-quality articles dedicated to all aspects of the latest outstanding developments in the field but not limited to Pharmacology-Toxicology, Pharmacognosy-Phytochemistry, Pharmaceutical, Analytical Pharmacy-Medicinal Chemistry, Natural Product Development, Clinical-Community Pharmacy, Management Pharmacy, and other Pharmacy aspects. This edition contains six articles consisting of Pharmacology-Toxicology, Pharmaceutical, Analytical Pharmacy-Medicinal Chemistry, Natural Product Development, and Management Pharmacy topics.Editorial boards are fully aware that there is still room for improvement in this edition, hence with all humility willing to accept constructive suggestions and feedback for improvements to the publication for the next editions. The editorial board would like to thank the University, all editors and reviewers, and contributors of the scientific articles who have provided the repertoire in this issue. We hope that all parties, especially the contributors of the articles, could re-participate for the success of the publication in the next edition in November 2019.